Expanding the Notion of Dialogic Trading Zones for Impactful Research: The Case of Women on Boards Research. (January 2017) - Sealy, Ruth; Doldor, Elena; Vinnicombe, Susan; Terjesen, Siri; Anderson, Deirdre; Atewologun, Doyin
Abstract : Debates about research impact highlight the importance of involving practitioners in research processes but are unclear as to how precisely to foster this dialogue. This paper considers how dialogic encounter can be encouraged through 'trading zones' where academics and practitioners collaborate. We draw on our experience of conducting research on women on boards for over 15 years to examine (a) how we established and evolved our role within trading zones in this field, achieving impact on policy and business practice, and (b) how we interfaced between trading zones and the academic field, thereby enabling cross‐fertilization of ideas between academics and practitioners. We contribute to literature on research impact by empirically examining and critically evaluating the key characteristics of trading zones. First, trading zones are theorized to be action‐oriented. Our analysis reveals how multiple stakeholders collectively redefine the action goals, illustrating the need to expand our understanding of relevant 'practitioners' beyond managers. Second, we find that durability of trading zones is crucial because it enables gestation of ideas and reframing problems. Third, we problematize the notion of psychological safety in trading zones, arguing that dialogic capability and the pursuit of impact require acceptance of trade‐offs and political manoeuvrings.